Mental Rotation of Digitally-Rendered Haptic Objects by the Visually-Impaired - Tivadar, Ruxandra I.; Chappaz, Cédrick; Anaflous, Fatima; Roche, Jean; Murray, Micah M. (Frontiers in Neuroscience, 2020)
In the event of visual impairment or blindness, information from other intact senses can be used as substitutes to retrain (and in extremis replace) visual functions. Abilities including reading, mental representation of objects and spatial navigation can be performed using tactile information. Current technologies can convey a restricted library of stimuli, either because they depend on real objects or renderings with low resolution layouts. Digital haptic technologies can overcome such limitations. The applicability of this technology was previously demonstrated in sighted participants. Here, we reasoned that visually-impaired and blind participants can create mental representations of letters presented haptically in normal and mirror-reversed form without the use of any visual information, and mentally manipulate such representations. Visually-impaired and blind volunteers were blindfolded and trained on the haptic tablet with two letters (either L and P or F and G). During testing, they haptically explored on any trial one of the four letters presented at 0°, 90°, 180°, or 270° rotation from upright and indicated if the letter was either in a normal or mirror-reversed form. Rotation angle impacted performance; greater deviation from 0° resulted in greater impairment for trained and untrained normal letters, consistent with mental rotation of these haptically-rendered objects. Performance was also generally less accurate with mirror-reversed stimuli, which was not affected by rotation angle. Our findings demonstrate, for the first time, the suitability of a digital haptic technology in the blind and visually-impaired. Classic devices remain limited in their accessibility and in the flexibility of their applications. We show that mental representations can be generated and manipulated using digital haptic technology. This technology may thus offer an innovative solution to the mitigation of impairments in the visually-impaired, and to the training of skills dependent on mental representations and their spatial manipulation.